Avoiding the Last Ride: can DUI Programming Address Multiple Risk Factors to Reduce Recidivism? - Gibson, Sandy (Journal of addictions & offender counseling, 2018)
A review of DUI education literature reveals weak evidence of effective interventions. New models are suggested that offer a combination of psychoeducation and evidence-based counseling approaches. Existing DUI programming models are explored with recommendations for areas for future research.